A Conversation with Martin Heidegger - Tallis, R. author. aut Link
XV, 226 p.
Keywords: Martin Heidegger is one of the most important as well as one of the most difficult thinkers of the last century. His masterpiece Being and Time has been described as the most profound turning point in German philosophy since Hegel. Raymond Tallis, who has been arguing with Heidegger for over thirty years, illuminates his fundamental ideas through an imaginary conversation, which is both relaxed and rigorous, witty and profound. The Conversation defines Heidegger's relevance to the philosophical agenda of the present century by illuminating his great contribution to our thinking about what it is to be a human being while identifying the weaknesses in his thought.